2016
DOI: 10.1159/000453154
|View full text |Cite
|
Sign up to set email alerts
|

Lipotoxic Palmitate Impairs the Rate of β-Oxidation and Citric Acid Cycle Flux in Rat Neonatal Cardiomyocytes

Abstract: Background/Aims: Diabetic hearts exhibit intracellular lipid accumulation. This suggests that the degree of fatty acid oxidation (FAO) in these hearts is insufficient to handle the elevated lipid uptake. We previously showed that palmitate impaired the rate of FAO in primary rat neonatal cardiomyocytes. Here we were interested in characterizing the site of FAO impairment induced by palmitate since it may shed light on the metabolic dysfunction that leads to lipid accumulation in diabetic hearts. Methods: We me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…16,17 Consequently, these studies suggested that EAT may lead to LV hypertrophy, left atrium (LA) dilation, diastolic and systolic dysfunction, irrespective of the presence of coronary artery disease (CAD). [16][17][18][19][20][21] Consistent with these fi ndings, CRP, an infl ammatory marker, was higher in the patient with diastolic dysfunction and was associated with increased EAT thickness in our study.…”
Section: Resultssupporting
confidence: 90%
“…16,17 Consequently, these studies suggested that EAT may lead to LV hypertrophy, left atrium (LA) dilation, diastolic and systolic dysfunction, irrespective of the presence of coronary artery disease (CAD). [16][17][18][19][20][21] Consistent with these fi ndings, CRP, an infl ammatory marker, was higher in the patient with diastolic dysfunction and was associated with increased EAT thickness in our study.…”
Section: Resultssupporting
confidence: 90%
“…Diets rich in high fat foods, especially saturated fats, cause obesity, leading to serious health problems, such as type 2 diabetes and lipotoxic cardiomyopathy [1]. It has been confirmed that the degree of lipid accumulation is linked to cardiac dysfunction of human diabetic hearts [2,3]. Palmitic acid (PA), the most common saturated long-chain fatty acid, triggers apoptosis in many cell types including cardiomyocytes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Palmitate also induces oxidative stress and ER stress independently of ceramide. For example, it increases diacylglycerol levels, which is associated with activation of protein kinase C (PKC), which inhibits the Kreb's cycle enzymes aconitase and isocitrate dehydrogenase [91]. Thus, the acetyl COA generated from peroxisomal and mitochondrial fatty acid beta oxidation accumulates in the cell, promoting acetylation of mammalian target of rapamycin complex (MTORC-1) and high mobility group box-1 (HMGB-1), as has been demonstrated in hepatocytes [92].…”
Section: Role Of Dietary Constituents In Inducing Tissue Oxidative Stress Lipid Peroxidation and The Metabolic Syndromementioning
confidence: 95%